Usefulness of the Multidimensional Edmonton Frail Scale to Assess Physical Limitations in Frailty Syndrome Among Patients with Reduced Ejection Fraction Related to Heart Failure - Karolina Studzińska; Piotr Wąż; Rita Hansdorfer-Korzon (Rehabilitacja Medyczna)
Introduction: According to the Heart Failure Association of the European Society of Cardiology, frailty syndrome is: “a multidimensional dynamic condition, independent of age, that renders a patient with heart failure vulnerable to stressors”. The Association recommends that all patients with heart failure be routinely assessed for the risk of developing or suffering from frailty. This is due to the fact that frailty syndrome has an adverse effect on the prognosis, treatment options and quality of life among patients with heart failure. Factors that may determine the presence of frailty include: clinical factors (e.g. the presence of additional comorbidities), physical-functional, cognitive-psychological and social limitations. A number of scales are available to assess frailty syndrome. To date, none have been validated in patients with heart failure. The Edmonton Frailty Scale (EFS) is a multidimensional scale that takes into account four factors identified as having a significant impact on the occurrence of frailty in heart failure. The physical factors included in the scale are functional capacity, assessed by the Timed Up and Go test (TUG) and functional independence, defined by a question about the degree of independence in performing selected activities of daily living.Study aim: The aim of this study is to assess the physical limitations included in the Edmonton Scale among a group of heartfailure patients with reduced ejection fraction.Materials and methods: The study included 106 patients diagnosed with heart failure having reduced ejection fraction (HFrEF< 40%). The mean age of the patients was 62.6 9.7 years. Men comprised 84% of the study population. Frailty was measuredusing the EFS on the day before or on the day of hospital discharge. Patients were assigned to one of the following groupson the basis of their Edmonton Score: non-frail, pre-frail and frail.Results: A predisposition to frailty was diagnosed in 44.3% of patients, while frailty was diagnosed in 12.3% of patients. Physical factors assessed by the EFS scale may significantly influence the pre-frail and frail diagnoses (p < 0.001). Among the components of functional independence, the activities that require special support for pre-frail and frail patients are: meal preparation, transportation and housekeeping. The results of the study may significantly influence the diagnosis of frailty and susceptibility to frailty in patients with heart failure (p < 0.001).Conclusions: Physical limitations assessed by the Edmonton Scale play an important role in the identification of pre-frailty andfrailty among patients with heart failure. Pre-frail and frail patients report difficulties in performing activities of daily living,with housekeeping, transportation and meal preparation as being the most difficult in both groups. The result of the Timed Upand Go test may have considerable impact on the diagnosis of frailty and susceptibility to frailty in patients with heart failure.